PREFERENTIAL SOLVATION OF L-ARABINOSE AND DL-MALIC ACID IN ETHANOL + WATER MIXTURES (2017)
By using the inverse Kirkwood-Buff integrals (IKBI) method, the differences between the local, around the solute and the bulk mole fractions of both solvents in saturated solutions of L-arabinose (compound 3) and DL-malic acid (compound 3) in ethanol (compound 1) + water (compound 2) binary mixtures were derived from their thermodynamic properties. Accordingly, it is found that these compounds are sensitive to preferential solvation effects; in this way, the preferential solvation parameter (dx1,3) for L-arabinose is slightly positive in water-rich mixtures but negative in those beyond 0.25 in ethanol mole fraction. In different way, the dx1,3 values of DL-malic acid are negative in almost all the compositions. The highest solvation by ethanol observed in water-rich mixtures for L-arabinose could be due mainly to polarity effects. Otherwise, the preference of these compounds for water in ethanol-rich mixtures could be explained in terms of the higher acidic behavior of water interacting with hydrogen-acceptor hydroxyl groups in L-arabinose and DL-malic acid.